(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2022)
Contemporary Ukrainian literature can meet most of the readers’ demands because genres that used to have a marginal status are becoming a productive component of the national speech art. Political fiction and alternative history belong to such genres. In the proposed study we will focus on the peculiarities of modeling post-apocalyptic societies — Ukrainian and Russian ones that appear on the geopolitical European map as a result of the Russian-Ukrainian war of the XXI century in the novel “Wall” by A. Tsapliienko. The novel is characterized by a supra-genre nature combining features of alternative history (it is a historical prediction, not an alternative to the past), anti-utopia, utopia, espionage and detective novels. Within the text, the category of “reality” appeals not to the past or the history itself but to the present, so the “key fact” starting the bifurcation process is absent and requires artistic fiction. A. Tsapliienko introduces two key events. The war ended leading to the emergence of two post-apocalyptic societies — Ukrainian and Russian ones. The first part of the work deals with the territory of the Wild Field from Rostov to Tahanroh. Let us note that the discourse of the “Wild Field” is quite vividly represented in Russian historiography. For the Russian historian, this is the territory of steppe peoples or “predatory hordes”. In this respect, Russia is understood as a European space. In A. Tsaplienko’s novel “The Wall”, the territory of Russia becomes the toxic land of the Wild Field, and the Russians become the Horde. The second part focuses on the city behind the Wall. The author models Ukrainian Eldorado as a space of civilization (“Every day in this country was really good”). So, post-apocalyptic societies emerging after the war are endowed with the following attributes: paradise (Ukraine) and “scorched land” (Russia). It manifests the antagonistic binomial “civilization — the wild world”.